Brand ambassador power: Can Twice's endorsement boost Scarlett Whitening's brand value? - Natassia, Eilentya (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Brand name plays a crucial role in the sustainability of a business. Business owners continually strive to enhance their brand name to make it more memorable to consumers. Scarlett Whitening is a well-known local skincare brand that utilizes Korean public figures to promote its products to the international market. This study investigates the impact of using a Korean brand ambassador on the brand value of Scarlett Whitening. To achieve this, the author distributed questionnaires to 105 respondents selected through judgmental sampling. The results indicated that the visibility and credibility of Twice girlband had no significant effect on brand value, whereas their attractiveness and power did. This study reveals that brand ambassadors influence brand value due to their attractiveness and power.